Suicidal ideation in medical students of Hebei province: prevalence and associated factors - Huang, Fanfan; Lu, Wenting; Zhao, Xiaochuan; Li, Na; Zhao, Tianyu; Guo, Shijie; Liu, Bufan; Ren, Ruojia; Yang, Li; Wang, Lan; Gao, Yuanyuan; Wang, Ran; et al. (Frontiers in Psychiatry, 2024)
Objectives: This study investigated the prevalence of suicidal ideation (SI) among Chinese medical students and its associated risk factors.Methods: A total of 6643 medical students (2383 males/4260 females) were recruited from a medical college in Hebei Province, China. Demographic data were collected via a selfadministered questionnaire. The Childhood Trauma Questionnaire Short Form (CTQ-SF) was used to evaluate childhood maltreatment (CM), and the Adolescent Self-Rating Life Events Checklist (ASLEC) was used to evaluate the stressful life events. Suicidal ideation was assessed using the Beck Scale for Suicide Ideation (BSSI). Univariate and multivariate logistic regression models were used to analyze the factors affecting SI.The prevalence of SI in medical students was 11.5% (763/6643). Multivariate logistic regression analysis revealed that SI was significantly associated with younger age, a female sex, being lovelorn, being introverted, experiencing CM during childhood, and experiencing stressful life events within the past 12 months. Of the five subtypes of CM, emotional abuse may have the strongest effect on SI (OR=2.76, 95% CI: 1.72-4.42). The joint effects of CM and stressful life events were significantly associated with an increased risk of SI (OR=5.39, 95% CI: 4.15-6.98).The prevalence of SI among medical students is high，and medical students who have experienced CM and stressful life events have a higher tendency towards SI. Screening for both CM and stressful life events may be an effective way of identifying individuals at high risk of SI.